Cardiac autonomic profile and cardiopulmonary response after maximal treadmill exercise testing with pre-exercise stretching - A. Souto Maior (Revista Andaluza de Medicina del Deporte, 2013)
Objectives. This study investigated the cardiac autonomic profile and cardiopulmonary responses at rest and after maximal treadmill exercise testing with or without pre-exercise stretching. Methods. Eight men (age = 24.6 ±mm 5.5 years; height = 179 ±mm 4.1 cm; mass = 78.1 ±mm 3.4 kg; body mass index = 24 ±mm 2.5 kg/m–2; body fat = 18.9 #mm 4.3%) completed a maximal treadmill exercise test under two randomly ordered conditions: pre-exercise stretching (PES) and no stretching (CONTROL). Electrocardiogram (ECG) and respired gas analysis were continuously recorded at rest, during, and for 5 min following exercise testing. The stretching exercises for the PES condition consisted of six passive stretches comprising upper and lower body muscle groups performed three times each for 30 sec with 10 sec passive rest between repetitions. Results. The results indicated that the rMSSD was significantly (p < 0.01) faster for the CONTROL versus the PES condition during the 5 min following exercise testing. Additionally, significantly lower low-frequency power (PES = 3.20 ±mm 1.14 ms2; CONTROL= 24.65 ±mm 7.57 ms2; p < 0.001) and total power (PES = 23.57 ±mm 7.41 ms2; CONTROL = 195.90 ±mm 46.37 ms2; p < 0.001) responses were visually detected for the PES versus CONTROL condition following exercise testing. Anaerobic threshold was decrease in PES when compared to CONTROL conditions. Conclusion. These data indicate that PES promotes dysfunction in the tonic cardiac autonomic regulation as evidenced by delayed parasympathetic reactivation, during the initial 5 minutes of recovery following maximal exercise testing.